The Influence of Work-Life Balance, Job Stress, Job Satisfaction, and Burnout on Job Performance - Doni Darwin; Aryana Satrya; Balakrishnan Parasuraman (LPPM Universitas Terbuka, 2025)
Purpose – This study aims to investigate the effect of work-life balance and job stress on job performance, with job satisfaction and burnout as mediating variables. The research focuses on employees of the Directorate General of Taxes in Indonesia, seeking to understand how internal psychological factors influence public-sector employee performance. Methodology – A quantitative approach was used, with data collected through a structured questionnaire distributed to 748 employees from various regional offices. The data was analyzed using Structural Equation Modeling (SEM) to evaluate both direct and indirect relationships among the variables. Findings – The results show that work-life balance significantly improves job satisfaction and reduces burnout, while job stress increases burnout and decreases job satisfaction. Job satisfaction fully mediates the relationship between work-life balance and job performance, while burnout significantly mediates the relationship between job stress and job performance. These outcomes highlight the importance of employee well-being in enhancing organizational performance. Originality – This study provides new insights into the mediating roles of job satisfaction and burnout in the public sector. It extends existing theoretical frameworks by offering a comprehensive model that reflects the realities of post-pandemic work environments, particularly in government institutions undergoing digital and structural transformation.